La escritura. Modo de empleo. - Noel-gaudreault, M. (Didáctica. Lengua y Literatura, 1997)
Ihis article is a kind of assessment. We will deal with the «Ten commandments of the writing teacher». More specifically, we will speak about the great principies that should guide people who have to teach writing. These principIes are inspired by the last progress in this domain.